2020
DOI: 10.1093/mnras/stz3245
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the fraction of core-collapse supernovae harbouring choked jets with high-energy neutrinos

Abstract: The joint observation of core-collapse supernovae with gamma-ray bursts shows that jets can be launched in the aftermath of stellar core collapse, likely by a newly formed black hole that accretes matter from the star. Such gamma-ray bursts have only been observed accompanying Type Ibc supernovae, indicating a stellar progenitor that lost its Hydrogen envelope before collapse. It is possible that jets are launched in core-collapse events even in the presence of a Hydrogen envelope, however, such jets are unlik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Although their constraints are not significant with their data sets, they demonstrated that the methods would put a meaningful constraint on the choked-jet SN fraction near future with better facilities of optical transient surveys (e.g., Vela Rubin Observatory 168 ) and neutrino telescopes (e.g., IceCube-Gen2 108 and KM3NeT 169 ), as discussed in Ref. 170…”
Section: Observational Constraints On Choked Jetsmentioning
confidence: 99%
“…Although their constraints are not significant with their data sets, they demonstrated that the methods would put a meaningful constraint on the choked-jet SN fraction near future with better facilities of optical transient surveys (e.g., Vela Rubin Observatory 168 ) and neutrino telescopes (e.g., IceCube-Gen2 108 and KM3NeT 169 ), as discussed in Ref. 170…”
Section: Observational Constraints On Choked Jetsmentioning
confidence: 99%
“…The underlying physics that lies in the heart of GRB explosions is still unknown, and it has long been thought that in a significant fraction of explosions, the GRBs jets are choked. The expected outcome of a choked GRB jet may be neutrinos and X-rays [ 78 ]. Thus, detected neutrinos can be used as targets of opportunity for THESEUS to constrain the expected rate of choked GRBs.…”
Section: Neutrino Detectorsmentioning
confidence: 99%
“…The underlying physics that lies in the heart of GRB explosions is still unknown, and it is long been thought that in a significant fraction of explosions, the GRBs jets are choked. The expected outcome of a choked GRB jet may be neutrinos and X-rays [77]. Thus, detected neutrinos can be used as targets of opportunity for THESEUS to constrain the expected rate of choked GRBs.…”
Section: Neutrino Detectorsmentioning
confidence: 99%